Concomitant systolic and diastolic alterations during chronic hypertension in pig. (June 2019) - Jozwiak, Mathieu; Meli, Albano C.; Melka, Jonathan; Rienzo, Mario; d'Anglemont de Tassigny, Alexandra; Saint, Nathalie; Bizé, Alain; Sambin, Lucien; Scheuermann, Valérie; Cazorla, Olivier; Hittinger, Luc; Berdeaux, Alain; et al.
Abstract: The mechanical and cellular relationships between systole and diastole during left ventricular (LV) dysfunction remain to be established. LV contraction-relaxation coupling was examined during LV hypertrophy induced by chronic hypertension. Chronically instrumented pigs received angiotensin II infusion for4weeks to induce chronic hypertension (133 ± 7 mmHg vs 98 ± 5 mmHg for mean arterial pressure at Day 28 vs 0, respectively) and LV hypertrophy. LV function was investigated with the instrumentation and echocardiography for LV twist-untwist assessment before and after dobutamine infusion. The cellular mechanisms were investigated by exploring the intracellular Ca 2+ handling. At Day 28, pigs exhibited LV hypertrophy with LV diastolic dysfunction (impaired LV isovolumic relaxation, increased LV end-diastolic pressure, decreased and delayed LV untwisting rate) and LV systolic dysfunction (impaired LV isovolumic contraction and twist) although LV ejection fraction was preserved. Isolated cardiomyocytes exhibited altered shortening and lengthening. Interestingly, contraction-relaxation coupling remained preserved both in vivo and in vitro during LV hypertrophy. LV systolic and diastolic dysfunctions were associated to post-translational remodeling and dysfunction of the type 2 cardiac ryanodine receptor/Ca 2+ release channel (RyR2), i.e., PKA hyperphosphorylation of RyR2, depletion of calstabin 2 (FKBP12.6), RyR2 leak and hypersensitivity of RyR2 to cytosolic Ca 2+ during both contraction and relaxation phases. In conclusion, LV contraction-relaxation coupling remained preserved during chronic hypertension despite LV systolic and diastolic dysfunctions. This implies that LV diastolic dysfunction is accompanied by LV systolic dysfunction. At the cellular level, this is linked to sarcoplasmic reticulum Ca 2+ leak through PKA-mediated RyR2 hyperphosphorylation and depletion of its stabilizing partner. Highlights: LV contraction-relaxation coupling is preserved during LV hypertrophy. SR calcium is leaking through PKA hyperphosphorylated RyR2 and depleted calstabin2. RyR2 contributes to the control of LV contraction-relaxation coupling.